Training on Making Mangrove-Based Beauty Soap Innovation Products in Sungsang IV Village, South Sumatra - Rozirwan, Rozirwan; Zia Ulqodry, Tengku; Ayu Eka Putri, Wike; Diansyah, Gusti; Winarta, Yoga; Yoga Nugroho, Redho (Universitas Ahmad Dahlan, 2025)
Background: In an effort to enhance the utilization of mangrove forests based on local coastal resources, a community service initiative was conducted in Sungsang Village, Banyuasin Regency, on 25-26 September 2024. The training focused on teaching 40 participants how to produce beauty liquid soap from Sonneratia caseolaris (mangrove) leaf extract. Contribution: This activity Contributes to improve the technical skills of making beauty liquid soap from mangrove plants as an effort to optimize the utilization of mangrove forest vegetation in Sungsang Village. Method: The method of this service activity is a training in making liquid soap through product prototype demonstration and direct assistance. Results: In general, the participants' knowledge about making beauty liquid soap from mangroves has increased after undergoing training activities. Conclusion: The pre-test and post-test evaluation of the 40 participants showed a significant improvement in their understanding, with the evaluation graph showing a shift from low to better levels of knowledge. While there were variations in the level of understanding about beauty liquid soap.